ANALISIS KEKERABATAN FENETIK CABAI HIYUNG DENGAN BEBERAPA KULTIVAR CABAI RAWIT - Nurul Mahmudah; Badruzsaufari Badruzsaufari (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
South Kalimantan is an area with abundant biodiversity, especially vegetable and medicinal commodities. Shark chili is one of the varieties of cayenne pepper (Capsicum frustescens L.) which is a typical commodity from South Kalimantan. Shark chili is a local chili commodity that has been named the hottest chili in Indonesia. The aim of this research is to distinguish the morphology of the chili chili with other varieties of cayenne pepper found in Indonesia based on morphological and special characters for further analysis of the genetic relationship. The diversity of chilies in the genus Capsicum is quite diverse so that in the division of chili species is further divided among several varieties or cultivars. Shark chili varieties with Nirmala varieties showed the highest similarity coefficient results compared to other chili varieties with a value of 6.32 while the value of the similarity coefficient of sharks with the lowest cadets with a value of 3.74. Environmental factors where cultivars grow differently even though they have the same place of origin and the adaptive nature of the genotype can affect the different appearance caused by the phenotypic emergent traits.